Hollywood, Nebraska - Jones, Kenneth (Playwright) (Broadway Licensing Global, 2025)
Two fortysomething actresses have returned to their once-thriving hometown in rural Nebraska. Jane is in from Los Angeles to check on her ailing mom, Alma. Andrea's back from New York City to bury her father. Distracted by two charismatic local men--a handsome widower and a rough-and-ready laborer--the old friends navigate complicated feelings about their careers, love, and loss, leading to an overdue showdown between Jane and her mother. HOLLYWOOD, NEBRASKA is a hope-filled, tears-and-laughter comedy about small towns and big dreams, parents and children, the urge to be creative, and the ache--and joy--of coming home.--